Institutional Integration and Productivity Growth: Evidence from the 1995 Enlargement of the European Union - Nauro F. Campos; Fabrizio Coricelli; Emanuele Franceschi (Institute of Labor Economics (IZA), 2021)
This paper studies the productivity effects of integration deepening. The identification strategy exploits the 1995 European Union (EU) enlargement, when all candidate countries joined the Single Market but one - Norway - did not join the EU. Our synthetic difference-in-differences estimates on sectoral and regional data suggest had Norway chosen deeper integration, the average Norwegian region would have experienced an increase in yearly productivity growth of about 0.6 percentage points. This method also helps determining the sources of heterogeneity, apparently inherent to integration, highlighting higher costs of the missed deeper integration for more peripheral regions and industrial sector.
Keywords: C33; F15; F55; O43; O52; 330; European Union; productivity growth; economic integration; institutional integration; European Economic Area